ANALISIS POLA PIKIR SISWA SMP DHARMA PANCASILA DALAM MENGHADAPI PERMASALAHAN - Suci Anggira; Syahlan Syahlan; Rosliana Siregar; Irvan Malay (MES: Journal of Mathematics Education and Science, 2026)
This study aims to analyse the mindset of pupils at Dharma Pancasila Junior High School in dealing with various academic and non-academic problems. The study employed a qualitative descriptive approach, involving pupils in Years 7, 8 and 9 as research subjects. Data collection techniques included observation, in-depth interviews, questionnaires and documentation. Data analysis utilised the Miles, Huberman and Saldaña model, which comprises data reduction, data presentation and drawing conclusions. The results of the study indicate that the majority of pupils exhibited characteristics of a growth mindset, such as a willingness to learn from mistakes, striving to find solutions, and accepting criticism as feedback for personal development. However, a number of pupils were still found to exhibit a fixed mindset, characterised by a tendency to give up easily when faced with difficulties, viewing ability as fixed, and avoiding challenges for fear of failure. Factors influencing pupils’ mindsets included the family environment, school culture, teacher support, peers, and previous learning experiences. This study recommends the implementation of teaching methods that foster a growth mindset through constructive feedback, reflective learning, and character building.